A Context for Public Comunication of Science and Tecnology in Colombia: from euro-centrics legacies to models for action (2011)
Public communication of science and technology has been consolidated in Colombia as a practical field and research field. Theory and empiric advances in democratization of knowledge are well-known, that deal with ethnocentric heritages and political, soci